Plug Formation and Dissociation of Mixed Gas Hydrates and Methane Semi-Clathrate Hydrate Stability - Hughes, Thomas John (University of Canterbury. Chemical and Process Engineering, 2008)
Gas hydrates are known to form plugs in pipelines. Hydrate plug dissociation times can be predicted using the CSMPlug program. At high methane mole fractions of a methane + ethane mixture the predictions agree with experiments for the relative dissociation times of structure I (sI) and structure II (sII) plugs. At intermediate methane mole fractions the predictions disagree with experiment. Enthalpies of dissociation were measured and predicted with the Clapeyron equation. The enthalpies of dissociation for the methane + ethane hydrates were found to vary significantly with pressure, the composition, and the structure of hydrate. The prediction and experimental would likely agree if this variation in the enthalpy of dissociation was taken in to account. In doing the plug dissociation studies at high methane mole fraction a discontinuity was observed in the gas evolution rate and X-ray diffraction indicated the possibility of the presence of both sI and sII hydrate structures. A detailed analysis by step-wise modelling utilising the hydrate prediction package CSMGem showed that preferential enclathration could occur. This conclusion was supported by experiment. Salts such as tetraisopentylammonium fluoride form semi-clathrate hydrates with melting points higher than 30 ℃ and vacant cavities that can store cages such as methane and hydrogen. The stability of this semi-clathrate hydrate with methane was studied and the dissociation phase boundary was found to be at temperatures of about (25 to 30) K higher than that of methane hydrate at the same pressure.